Effect of Kalzoral preparation on prevention of parturient paresis relapse, in dairy cows - KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), H.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ), N.; CHRISTODOULOPOULOS (Γ. ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΣ), G.; PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ), N.; PAPASTERIADIS (Α. ΠΑΠΑΣΤΕΡΙΑΔΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
This research describes 20 cases of cows with parturient paresis (controls), which were treated with intravenous administrations of calcium gluconate and dextrose, and intramuscular injection of vit. D3 . In 20 other cases (experimental group), a solution of 250g Kalzoral was administrated orally, after the treatment mentioned above. Thiw Klzoral is a preparation of Dr E. Graeub AG, Bern Switzerland, containing 22% Ca, 4% Ρ, 5% Mg, 200.000 IU/kg vit D3 , flavours and taste improvements. The administration of Kalzoral was repeated twice, in the same dose, 24 and 48 h after the first administration. The levels of Ca, Ρ, Mg Κ and Na in the blood serum of the cows were measured before starting the treatment and also 24 and 72 h after it. Both groups, during the disease presented hypocalcemia (serum Ca<6,5 mg/dl), hypophosphatemia, mild hyponatremia, and normal concentrations of Mg and K. Six anomals (30%) of the controls group had a relapse within the first 24 h after the treatment. There was no relapse in the experimental group. The concentration of Ρ of the experimental cows came back to normal, the first day after the initial treatment while that of the controls, on the third. The concentration of Mg and Κ in the blood serum of all animals was found to be normal always. The initial hyponatremia of both groups remained at the same level, as it was indicated by the last two measurements and it appeared no connection to the parturient paresis. It was considered to be the result of insufficient addition of NaCl in the animals diet.